Distribusi Geografis Tungau Parasit Nyamuk Aedes Sp. di Daerah Endemis Demam Berdarah Dengue di Propinsi Jawa Tengah - Bambang Heru Budianto; Retno Widiastuti (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2012)
The geographical distribution patterns of parasitic mites determine the types of parasitic mites that should be developed in these endemic geographical regions. Types of parasitic mites and the patterns of geographic distribution of parasitic mites of Aedes sp. in dengue endemic areas in Central Java Province have not been determined yet. The purpose of this research was to determine the parasitic mite and geographical distribution patterns in dengue endemic areas in Central Java Province. All stages of the experiment were conducted by using a survey method with random sampling technique. Sampling area for Semarang City included the counties of Central Semarang and Tembalang, whereas for Banjarnegara including the villages of Krandegan, Kutabanjar, Parakancanggah, and Sokanandi, and the county of Karanganyar City, Karanganyar. Larvae, pupae and adult stages of Aedes mosquitoes. were sampled during the rainy season. Types of parasitic mites were identified using Walter & Proctor (1999), Pesic (2003) and Gerecke (2004) references. The average value and variance were analyzed for the number of each stage to determine the geographic distribution pattern of parasitic mites. The infection ability was determined by the average intensity of parasitic mites and the prevalence value. The results demonstrated that the families of parasitic mites that infect the larvae of Aedes sp. in dengue endemic areas in Central Java Province were Pionidae 1, Histiostomatidae, Hydryphantidae, Hydrachnidae 1, Arrenuridae, Hydrachnidae 2 and Pionidae 2.  Based on the frequency of occurrence, prevalence and the ability to infect, it was concluded that family Histostomatidae is a potential candidate for biocontrol agent of Aedes sp larvae. The distribution pattern of  parasitic mite families in endemic areas of dengue fever in Central Java Province, showed a random distribution pattern.